1984 Report of Agricultural Research, Southeast Kansas Branch Station - R. W. Dougherty; K. W. Kelley; L. W. Lomas; J. L. Moyer; D. W. Sweeney (Kansas Agricultural Experiment Station Research Reports, 1984)
Through annual research reports the Southeast Kansas Branch Experiment Station attempts to keep the area's consumers and producers of agricultural products informed on the Station's research accomplishments. In serving the area, we conduct research at fields located at Parsons, site of headquarters; at Mound Valley, the original. location of the Branch Station; and at Columbus, which has been in the Kansas State University research system for over 60 years. This report for 1983 covers five areas of research emphasis: Beef Cattle, Crops, Forages, Soil and Water Management, and Crop Varietal Development. We sincerely hope that it will be useful to area producers and consumers, industry cooperators, Extension personnel and others.
Keywords: wheat; grain sorghum; soybeans; forage; soil; water management; beef cattle